Insights into Cultural, Social, and Psychological Factors that Influence Foreign Language Learning - Almosa Abdulrahman (BATARA DIDI : English Language Journal, 2023)
The significance of socio-cultural and psychological aspects in acquiring foreign languages is receiving more attention. Foreign language education has become a significant component of the global academic system, wherein people acquire languages order than their first language in the classroom. Different factors have been analyzed to impact learning a second language in the classroom significantly. This article explores various social, cultural, and psychological factors influencing students’ performance in a foreign language. The focus is to evaluate the impacts of these factors and assess how the participants rate the effects. The study is quantitative, and data was gathered through a structured questionnaire ranked using the Likert Scale. A total of 200 participants were randomly selected for the study, including twenty teachers that facilitated the participation of the students, mainly during the distribution of the questionnaire through digital systems. Analysis was conducted using appropriate statistical tools, such as percentage values, mean and standard deviation. A total of nine social, cultural, and psychological factors were analyzed, including interaction patterns in the classroom, rapport with teachers, lack of motivation, the attitude of learners, general cultural concerns, initiation issues, self-consciousness, fear of making mistakes, and classroom anxiety. These factors exert impact at varying degrees on the learning of English as a foreign language in the classroom. The analysis indicates that psychological factors exert more influence on the students, followed by social factors.